The complete chloroplast genome sequence of Camellia granthamiana. Issue 2 (3rd July 2019) - Jiang, Zhenzhong; Jiao, Peng; Qi, Zhuo; Qu, Jing; Guan, Shuyan
Abstract: Camellia granthamiana is a rare and endangered plant peculiar to China, and a total of 5 plants have been found at present. Based on the next generation sequencing, the whole chloroplast (Cp) genome of (Camellia granthamiana Sealy) of Camellia oleifera was constructed.In this study, the complete chloroplast (cp) genome of Camellia granthamiana was assembled based on next generation sequencing.The cp genome was 157, 001 bp in length, including a large single copy (LSC) region of 70, 387 bp, a small single copy (SSC) region of 18, 296 bp and a pair of inverted repeats (IRs) of 52, 082 bp. The genome contained 135 genes, including 90 protein-coding genes, 37 tRNA genes and 8 ribosomal RNA genes. The majority of these gene species occurred as a single copy.